Principles of Organization of the Ukrainian Language Extracurricular Work in the Process of Profile Education - Didenko, Nataliia (Pedagogical Discourse, 2015)
Definition and foundation of basic didactic principles of organization of extracurricular work in specialized philological classes based on the analyses of scientific and methodological literature is given in the publication. The article is aimed at analysis of scientific and educational literature that describes the use of basic principles of organization of Ukrainian language extracurricular work in the process of profile education and its content. Research methodology includes the use of theoretical and practical research methods. The question of research content of extracurricular work in domestic and foreign lingvo didactics is considered. Trends of organization of extracurricular work in profile school, formed on the basis of specific principles are outlined. Definitions of such concepts as «principle», «principles of training and education», «special principles of extracurricular work in specialized philological classes» are presented. Basic principles of extracurricular work in specialized philological classes that are methodological guidance in productive extracurricular work organisation based on the analysis and synthesis of the mentioned sources are defined. It is noted that all principles are interrelated and supplement each other.They comprise a coherent set of principles for extracurricular work in profile school. Nature of the interrelations and interdependence are explained. It is focused on task-oriented, consistent and systematic impact on the formation of linguistic identity, increase of motivation, future profession orientation. The conclusion about the urgency of the problem within the period of educational modernization strategy and prognosis of future research is carried out.